Pengaruh Ketersediaan Obat, Lokasi, dan Kualitas Pelayanan terhadap Keputusan Pembelian di Toko Obat Zahwa - Zahwa Rahmadina; Yandra Rivaldo; Mohamad Aras (Jurnal Manajemen Riset Inovasi, 2026)
This study investigates the influence of drug availability, location, and service quality on consumer purchasing decisions at Toko Obat Zahwa Batam. The phenomenon underlying this research is a significant decline of 23.3% in transactions at Toko Obat Zahwa over three years (2022–2024). A quantitative approach with survey method was employed, involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using IBM SPSS 26. The results indicate that drug availability has a positive and significant effect on purchasing decisions (t = 5.390; sig. = .000), service quality has a positive and significant effect (t = 4.700; sig. = .000), while location does not significantly influence purchasing decisions (t = –0.556; sig. = .579). Simultaneously, all three variables significantly affect purchasing decisions (F = 38.203; sig. = .000) and explain 53.0% of the variance (Adjusted R² = .530). The dominant influence of drug availability confirms the need-driven nature of pharmaceutical retail purchases, while the non-significant effect of location reflects habitual buying behavior among loyal consumers. These findings provide practical implications for independent drug store management in competitive markets.